2014
DOI: 10.3851/imp2777
|View full text |Cite
|
Sign up to set email alerts
|

On-Treatment Low Serum HBV RNA Level Predicts Initial Virological Response in Chronic Hepatitis B Patients Receiving Nucleoside Analogue Therapy

Abstract: Low serum HBV RNA level at week 12 of nucleoside analogue therapy independently predicts initial virological response in treated chronic hepatitis B patients. Serum HBV RNA levels may thus be useful for optimizing treatment of chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 20 publications
6
69
2
Order By: Relevance
“…However, 2 other reports by Huang et al, showed that serum HBV RNA was undetectable in all the 19 studied patients and only found in 40% (21/52) of the untreated ones (11,17). The difference between the results of the current study and those of others may be attributed to the differences between the studied populations.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, 2 other reports by Huang et al, showed that serum HBV RNA was undetectable in all the 19 studied patients and only found in 40% (21/52) of the untreated ones (11,17). The difference between the results of the current study and those of others may be attributed to the differences between the studied populations.…”
Section: Discussioncontrasting
confidence: 89%
“…It also showed that serum HBV RNA level is a valuable early predictor for the occurrence of antiviral resistant mutations (10) and reactivation of chronic hepatitis B (CHB) after antiviral therapy cessation (8). Serum HBV RNA is a novel biomarker of HBV infection and is useful to optimize antiviral strategies (9,11). However, to understand the factors affecting its serum level and detection, and its biological and clinical significance, large cohorts of untreated patients are required.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, serum HBV RNA has been reported as an important potential predictor of the YMDD resistance mutation [11], efficacy [9,[12][13][14] and prognosis [10] of CHB treatment. Whether dynamic changes in serum HBV RNA can be used as a potential marker for the safe discontinuation of NAs therapy remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in addition to HBV DNA, HBV RNA has also been detected in the serum of chronic hepatitis B (CHB) patient [7][8][9][10][11][12][13][14]. However, the life cycle of HBV cannot fully explain the generation of serum HBV RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, before and during treatment with nucleos(t)ide analogue (NA) or pegylated interferon alfa (PEG‐IFN), a correlation between serum HBV RNA and the transcriptional activity of cccDNA was demonstrated 6. In addition, serum HBV RNA levels were found to be associated with the probability of response to treatment with either NAs or PEG‐IFN 2, 4, 7, 8, 9. However, before the further development of serum HBV RNA as a response‐predicting marker, it is mandatory to evaluate which factors which may influence HBV RNA levels in individuals who are eligible for treatment.…”
mentioning
confidence: 99%